2009
DOI: 10.1186/1471-2369-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease in Thai adults: a national health survey

Abstract: BackgroundThe prevalence of patients with end stage renal disease (ESRD) who need dialysis and/or transplantation has more than doubled in Thailand during the past two decades. It has been suggested that therapeutic strategies to reduce the risk of ESRD and other complications in CKD are now available, thus the early recognition and the institution of proven therapeutic strategies are important and beneficial. We, therefore, aimed to determine the prevalence of CKD in Thai adults from the National Health Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
8
40
5
Order By: Relevance
“…A similar association has been reported in a study in Taiwan [15], where 62% of the affected population was male. However, the majority of published studies have shown female-dominant CKD cohorts [4,22,23]. Further research is needed to determine the reasons for male dominance in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…A similar association has been reported in a study in Taiwan [15], where 62% of the affected population was male. However, the majority of published studies have shown female-dominant CKD cohorts [4,22,23]. Further research is needed to determine the reasons for male dominance in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Even for the subjects of CKD stage 1-2, hazard ratios (HR) for all-cause mortality were still significantly higher in those with overt proteinuria compared to those with negative proteinuria. As for the elderly population with CKD, Hwang et al further proved that these populations had significantly higher HR of 1.5, 2.1 and 2.6 for groups with eGFR of [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Regarding the impact of CKD on medical care cost, CKD patients were reported to have higher chances of cardiovascular events and hospitalizations. Taiwan BNHI data showed that patients with CKD had higher rates of outpatient visits, hospitalizations and medical expenses compared to patients without CKD (unpubl.…”
Section: Impact Of Ckd/esrd On Public Healthmentioning
confidence: 99%
“…Based on the third National Health Examination Survey (NHES III), a national representative survey of the Thai population, the prevalence of age-adjusted CKD stage III-V in the year 2004 was 8.9%, and the prevalence of CKD stage V was 0.2% [2]. The report also showed the highest prevalence of CKD in the northeastern region of Thailand (10.8%).…”
Section: Introductionmentioning
confidence: 79%
“…Since the study hospital is a small 30-bed hospital that is responsible for healthcare services of 20,394 people in the area, these 63 patients constituted all CKD stage V patients in the area, indicating a 0.3% prevalence of CKD stage V, a little greater than the 0.2% prevalence given in the national report [2]. The patients were invited to participate in the study, and all of them gave informed consent and agreed to participate.…”
Section: Resultsmentioning
confidence: 99%